Cross -Cultural Currents: Exploring the Intersection of Bengali and English Literature (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The intersection of Bengali and English literature represents a remarkable example of cross-cultural literary dialogue, evolving through historical circumstances, colonial encounters, and postcolonial negotiations. This interaction began during the 19th century, a period marked by the Bengal Renaissance, when English education and Western literary forms were introduced under British colonial policies. This period witnessed the emergence of bilingual intellectuals who embraced Western ideologies while seeking to preserve indigenous traditions. Writers such as Michael Madhusudan Dutt and Bankim Chandra Chattopadhyay pioneered this literary synthesis, incorporating elements of European romanticism, realism, and epic poetry into Bengali works, thereby creating a distinctive hybridized literature.One of the most influential figures in this dialogue was Rabindranath Tagore, whose English translation of Gitanjali earned global recognition and positioned Bengali literature on the world stage. Tagore’s writings exemplify the fusion of Eastern spirituality with Western modernist aesthetics, reflecting both cultural adaptation and resistance. Similarly, Toru Dutt’s poetry in English, deeply rooted in Indian sensibilities, became an early marker of India’s literary cosmopolitanism. Translation played a pivotal role in this process, not only in disseminating Bengali literature internationally but also in shaping English perceptions of Indian culture (Chakraborty, 2020).In the contemporary era, this cross-cultural engagement persists through diasporic and postcolonial writings. Authors like Amitav Ghosh and Jhumpa Lahiri explore questions of identity, migration, and belonging within transnational frameworks, extending the legacy of cultural hybridity. Their works illustrate how linguistic and cultural negotiations continue to influence literary production, demonstrating that the Bengali-English interface is an ongoing and dynamic phenomenon rather than a historical relic (Mukherjee, 2021). However, these exchanges also raise critical debates around authenticity, cultural appropriation, and the power dynamics embedded in translation practices. Addressing these concerns requires re-evaluating literary hierarchies and acknowledging the agency of bilingual and multilingual creativity.This paper seeks to analyze the historical evolution, thematic intersections, and cultural implications of this literary dialogue. It argues that the convergence of Bengali and English literature not only shaped nationalist consciousness during colonial times but also continues to redefine global literary narratives in an age of interconnectedness. By exploring this phenomenon, the study contributes to broader discussions on comparative literature, postcolonial theory, and cultural studies, reaffirming the significance of literature as a medium of cross-cultural understanding and negotiation.